ANTI JAMUR HASIL FERMENTASI Streptomyces Isp. 192 PADA MEDIA PATI DAN GLUKOSA - S Djajasupena; O Suprijana; S.A Desak Gede; A T.Karossi (Research Center for Chemistry - LIPI, 2009)
Streptomyces ISP 192 was family of Actinomycetes which was high value microorganism that industrially important because it was capablefor producing ofbioactive compound that very useful in the field of medicine that is antibiotic. Recently antibiotic is still eligible medicine to overcome infection disease, but many more organism that cause of infection have been resistant against various antibiotics so need to look for a new antibiotic. This research cover cultivation of Streptomyces ISP 192 in potato dextrose agar (PDA) medium then fermentation by 250 mL shakeflash with 50 ml working volume. Microorganism was inoculated in fermentation medium MF1 and MF2 that contain (%)w/v variation of starch and glucose to bea source of carbon as soon as (%)v/v variation of inoculum. Fermentation process was conducted in 30°C temperature with 150 rpm shaking for seven days. Regularly for each 24 hour, sample was taken for analyzing ofpH, glucose and protein concentration, dry weight of cell and testing of anti fungal activity against Candida albicans, Microsporum gypseum, Tricophyton sp. dan Aspergillus niger. The result of research showed Streptomyces ISP 192 has high anti fungal activities against Candida albicans, Microsporum gypseum, Tricophyton sp., in usage of fementation media MF2 with 10 % glucose to be a carbonsource and 10% inoculum but not have activited against Aspergillus niger. Biosynthesis of antibiotic anti fungal start from 4th to 6th day that indication indecreasing of glucose and protein concentration as well aspH.Keywords: Streptomyses ISP 192, fermentation, testing ofantifungal activities.